Primary safety results from the LEADLESS Observational Study. Issue 9 (19th January 2018) - Sperzel, Johannes; Defaye, Pascal; Delnoy, Peter-Paul; Garcia Guerrero, Juan Jose; Knops, Reinoud E; Tondo, Claudio; Deharo, Jean-Claude; Wong, Tom; Neuzil, Petr
Abstract: Aims: A prospective, single-arm, multicentre, post-market study was conducted to confirm the short-term safety of the Nanostim™ leadless pacemaker (LP). In this study, we report the primary results of the LEADLESS Observational Study. Methods and results: Subjects meeting VVIR pacemaker indications were enrolled and followed up after successful LP implantation, prior to discharge and post-implantation at 90 days, 180 days, and every 6 months thereafter for the assessment of adverse events. The primary safety endpoint was evaluated in terms of freedom from serious adverse device effects (SADEs) at 6 months in 300 subjects. Data for all enrolled subjects were also presented. A total of 470 subjects were enrolled (75.8 ± 13.1 years, 62.8% male). The study paused in April 2014 following the occurrence of perforation events that led to changes in the protocol and investigator training. Freedom from SADEs, evaluated in 300 subjects enrolled post-pause, was 94.6% (95% confidence interval 91.0–97.2%) and demonstrated non-inferiority to a performance goal of 86% ( P  < 0.0001). Eighteen SADEs were observed in 16 (5.3%) subjects. The most frequently occurring events were cardiac perforation (1.3%), device dislodgement (0.3%), and vascular complications (1.3%). In the 470 subjects, 34 similar SADEs were observed in 31 (6.6%) subjects. After stratifying the results in relation to the study pause, there was a statistically significant difference in the final LP location (septum vs. apex) ( P  < 0.0001) and the number of repositioning attempts (<2 vs. ≥2) ( P  = 0.05) and a decreasing trend in the rates of cardiac perforation and device dislodgement. Conclusion: The primary safety endpoint at 6 months was successfully met for the Nanostim LP. The occurrence of cardiac perforation and device dislodgement declined after changes following the study pause.